E-081 Acuity classification system for neuro-interventional surgery cases in the evolving world of hyperacute endovascular stroke care. (22nd July 2019) - Linn, A; Gujrati, Y; Qahwash, O; Razak, A
Abstract : Introduction/Purpose: NIS (Neuro-Interventional Surgery) as a sub-specialty has undergone a tremendous transformation in many regards since its early beginnings. A major area of change includes the demand for the NIS provider to be immediately available while on call, particularly as it pertains to MER (mechanical endovascular reperfusion) for ELVO (emergency large vessel occlusion) type acute ischemic strokes. MER for ELVO's can be regarded amongst the most pressing hyperacute emergencies in all of medicine, thereby placing a substantial demand on the providers and healthcare facilities offering this treatment. As endovascular stroke care continues to evolve, so too will the number of hyper-emergent NIS cases which have already risen dramatically, leading to an increased potential for NIS provider burnout. We propose an acuity classification system which may assist individual healthcare systems providing NIS care to better assess the degree of change over time and prepare for the future. Materials and methods: We retrospectively reviewed just under 21-months of NIS cases completed at our facility from 7/01/2017 through 3/22/2019. These cases were classified into four categories based upon their level of acuity with regard to how quickly the patient ought to be brought to the neuro-angiography suite for the procedure per the NIS provider's discretion. The type of NIS case deemed 'hyper-emergent' will vary from provider to provider, but by using a classification system based upon the acceptable degree of time delay from the procedure's decision start point to the patient's arrival to the neuro-angiography suite, unique data for an individual healthcare system can be generated and compared over time. In general, hyper-emergent NIS cases include all ELVO's, as well as select cases of intracranial and extracranial hemorrhage. Results: Our healthcare system experienced a notable increase in the number and percentage of hyper-emergent NIS cases relative to less acuity level cases. In our facility, this data will be used for internal healthcare system review for various purposes, including resource allocation and NIS provider on-call coverage assessments. As these data points will most certainly be facility specific, only our facility's current and recent acuity level percentage breakdown is listed for example purposes. For reference, our elective caseload volume has stayed relatively stable over time, confirming a true increase in the hyper-emergent caseload volume by number and percentage. Conclusion: Our healthcare system has observed an increase in the number and percentage of hyper-emergent NIS cases over time, chiefly as a result of the research-driven expansion of the indications and selection of ELVO patients for MER. As hyper-emergent NIS caseload volumes continue to increase, comparison of current and prior caseload acuity trends may allow the individual healthcare system to better optimize for efficient resource allocation, provider coverage determination, and fair on-call provider reimbursement. Disclosures: A. Linn: None. Y. Gujrati: None. O. Qahwash: None. A. Razak: None.